1986
DOI: 10.1017/s0317167100036635
|View full text |Cite
|
Sign up to set email alerts
|

Early Onset Parkinson's Disease in Saskatchewan - Environmental Considerations for Etiology

Abstract: ABSTRACT:The cause of idiopathic Parkinson's Disease (PD) is not known but it is believed to be related to some environmental agent(s). Given a long preclinical interval and onset of symptomatology around age 60 years, it becomes impossible to identify and analyze all prior environmental factors satisfactorily. To circumvent these difficulties we evaluated the childhood environment in those PD patients whose symptoms began at age 40 years or earlier. Twenty-one such cases were born and raised in the province o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
1
4

Year Published

1988
1988
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 30 publications
4
47
1
4
Order By: Relevance
“…[3][4][5][6][7] Few investigations have evaluated a direct relationship between occupational chemical exposures and PD. Toxicant-induced parkinsonism may have atypical features, 8,9 but this factor has not been investigated systematically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7] Few investigations have evaluated a direct relationship between occupational chemical exposures and PD. Toxicant-induced parkinsonism may have atypical features, 8,9 but this factor has not been investigated systematically.…”
Section: Discussionmentioning
confidence: 99%
“…Specific occupations (agriculture, education, health care, mining, and welding) and toxicant exposures (solvents and pesticides) were identified a priori as putative risk factors for parkinsonism based on mechanistic theories or information from prior publications. [3][4][5]8,9,[15][16][17][18] …”
Section: Human Subjects/risk Factor Interviewsmentioning
confidence: 99%
“…Other studies have demonstrated that drinking well-water and living in a rural setting, both of which may increase exposure to agricultural pesticides, increase the risk of developing PD (Rajput et al, 1986;Barbeau et al, 1987;Rajput et al, 1987;Golbe et al, 1990;Semchuk et al, 1991). In addition, exposure to pesticides used in the home has been linked to PD (Stephenson, 2000).…”
mentioning
confidence: 99%
“…However, since the clinical characteristics, the pattern of progression of the symptoms and the development of wearing-off and on-off fluctuation to levodopa in one particular patient, made us to suspect that the fungicide is associated, not with manganese poisoning but with idiopathic parkinsonism. Previous rural living also appears to be associated with the development of the illness in younger patients 15 . Moreover, this precocious form of the illness appears to have certain clinical characteristics which distinguish it from the laterdeveloping form 9 .…”
Section: The Cause Of Parkinson's Disease (Pd)mentioning
confidence: 99%
“…In the last few years, a series of epidemiological studies have suggested that PD is more prevalent among individuals who live in rural areas 10 " 1215111 . Among the possible causative factors associated with rural living, consumption of well water 15 "* and exposure to pesticides 2 -*' 16 have been frequently cited. In a previous study carried out by our group, signs of parkinsonism were detected in agricultural workers who had been exposed to the fungicide maneb 7 .…”
Section: The Cause Of Parkinson's Disease (Pd)mentioning
confidence: 99%